The Notary Role in Making Working Contract of Pharmacy with Capital Owner - Ahmad Mufti Damara; Umar Ma'ruf; Sri Kusriyah; Ira Alia Maerani (Sultan Agung Notary Law Review, 2022)
A notary is a public official in charge of representing the state and is a profession, so that a notary gains the trust of both the government and the public. The value of this trust which is owned by a notary as a public official is not only obtained because of the law in making authentic deeds. This study wants to answer the problem of how the role of a notary in making a pharmacist work contract with the owner of capital for a dispensary in Grobogan district, how the constraints and solutions for the role of a notary in making a pharmacist work contract for a pharmacist in Grobogan district. The approach method used is sociological juridical, analytical descriptive research specifications. The data used are primary and secondary data, the data is accessed qualitatively and research problems are analyzed using the theory of legal protection and the theory of legal certainty. Based on the results of the study, it can be concluded (1) the role of a notary in making a work contract is that a notary has the authority to make an authentic deed regarding all agreements, and provisions required by legislation and/or desired by the interested parties to be stated in an authentic deed.